Three-dimensional geoelectric model of the Golovanevsk suture zones of the Ukrainian Shield - Shyrkov, B.I.; Burakhovich, Т.К.; Kushnir, A.N. (Geofizicheskiy Zhurnal, 2017)
Thorough three-dimensional deep model has been plotted for the first time for the Golovanivsk suture zone of the Ukrainian shield and adjacent area applying Mtd3fwd R. L. Mackie's program based on geophysical experiment as MTS and MVP investigations. Anomalies of electro-conductivity in the Earth crust coinciding spatially with deep fault zones have been allocated. It has been confirmed that outside the limits of the GSZ heterogeneous earth crust and upper mantle are both observed. It has been shown that the areas of anomalously high resistance partially correspond to massifs of crystalline rocks (the Uman, the Korsun-Novomirgorod, the Novo-Ukrainian) in the Earth's crust and upper mantle. Anomalies of high electrical conductivity with ρ = 2 ¸ 250 Ohm · m in the crust have been revealed, which coincide with deep fault zones: Talne, Pervomaisk, Vradievka, Gvozdavka, Zvenigorod-Bratsk, Simla, Subbotsko-Moshorinka; which are represented up to the depths of 2,5 km by sub-vertical structures and deeper — mainly by sub-horizontal layers. Outside the GSZ heterogeneous earth crust and upper mantle are observed as regional Chernivtsi-Korosten and Kirovograd anomalies of electro-conductivity. The geological structure of the GSZ and its electrical conductivity confirm the collision model of crust formation of the central part of the Ukrainian shield. The low resistivity anomalies are confined to the elongated stripes and areas of abundance of the graphitized rocks and metasomatic zones extended along the fault zones. Within their boundaries most part of ore deposits and ore manifestations in the region are found. The obtained distribution of electrical conductivity in the Earth's crust and upper mantle of Golovanivsk suture zone can be used for the plotting of deep geological and tectonic models and predictive metallogenic maps and schemes of the USh, as well as for an explanation of geodynamic processes in the region.